Understanding the Crucifixion from an Islamic Perspective: Abu Zahrah’s Thought and Contemporary Interfaith Dialogue - Badrun, Muhammad; Afrudin; Muhammad, Fazlurrahman (Yayasan Letiges Konsultan Sosial, 2025)
Crucifixion is a significant theme in both Christianity and Islam, representing one of the most debated theological issues between the two traditions. In Christianity, the crucifixion of Jesus Christ is regarded as the foundation of salvation, while in Islam the Qur’an explicitly rejects this event, affirming instead that Jesus was saved by God. This doctrinal divergence has generated long-standing debates among scholars and provides a compelling context for interfaith dialogue. The purpose of this research is to analyze the perspective of Muhammad Abu Zahrah, a prominent twentieth-century Muslim scholar, on the crucifixion and to identify its implications for Islamic theology and interreligious engagement. This research uses a qualitative approach through the Systematic Literature Review (SLR) approach using the SPIDER formula. This study identifies and synthesises relevant literature from Scopus, DOAJ, Google Scholar, ResearchGate, and Al-Azhar repositories, covering publications from 2000-2024. The collected sources were analysed through thematic content analysis to identify core theological principles, comparative interpretations, and implications for interfaith dialogue. The findings reveal that Abu Zahrah consistently emphasized the theological meaning of the crucifixion narrative as a rejection of atonement theology, an affirmation of tawhid, and a demonstration of divine protection for prophets. His approach integrates theological, historical, and sociological dimensions, distinguishing his thought from classical scholars and offering a framework for constructive interfaith dialogue. The study concludes that Abu Zahrah’s interpretation remains relevant for contemporary Islamic studies by providing fresh insights into theological renewal and interreligious cooperation. However, the research is limited to textual analysis without empirical validation in interfaith practice, suggesting that future studies should explore the practical application of Abu Zahrah’s thought in modern interreligious contexts.